Supplying new cocoa planting material to farmers: a review of propagation methodologies - Sena Gomes, A.R.; Andrade Sodré, G.; Guiltinan, M.; Lockwood, R.; Maximova, S.; Laliberte, B.; End, M. (Bioversity International, 2015)
The review, coordinated by Bioversity International, presents an impartial, evidence-based review of cacao propagation methods, to serve as a basis for the assessment and implementation of strategies for providing farmers with quality planting materials, adapted to current and future needs (cultural, institutional, technical, environmental and financial). It describes the various propagation methods available for the production and supply of large numbers of cacao plants to growers. It is hoped that the result of the efforts of the key authors provides a basis to build on for case-specific recommendations. As the supply of new improved planting material to farmers is at the heart of improving cocoa productivity and modernizing the crop, we hope that the information in the review will make its way into national cocoa plans, and help to make cocoa farming more attractive and more sustainable.